Physiologic requirement for iron in pregnant women, assessed using the stable isotope tracer technique - Cai, Jie; Ren, Tongxiang; Lu, Jiaxi; Wu, Jinghuan; Mao, Deqian; Li, Weidong; Zhang, Yu; Li, Min; Piao, Jianhua; Yang, Lichen; Ma, Yuxia; Wang, Jun; et al. (Nutrition & metabolism, 2020)
Background Knowledge of the physiologic requirement for iron, the core index for the formulation of a dietary reference intake (DRI), is of great importance for the health of a pregnant woman and her fetus, and can help a mother accurately plan her iron supplementation. However, direct measurements of the physiologic requirement for iron during pregnancy are still lacking. Method Eleven women of reproductive age from Hebei Province, China, who planned to become pregnant in the near future, were enrolled between January and March 2015 and included in the final analysis. Subjects participated in a 2-week metabolic trial in which they consumed 50 mg of the stable isotope 58 Fe, and were then followed for ~ 2 years. The abundance of 58 Fe and the total iron concentration in the circulation were measured using Multi-collector Inductively-Coupled Plasma Mass Spectrometry and Atomic Absorption Spectroscopy, respectively. The physiologic requirement for iron during pregnancy was then calculated by the formula derived from our previously published work. Results The mean physiologic requirement for iron in the 11 subjects, across their entire pregnancies, was 3.05 mg.d − 1 in total and 44.0 μg.kg − 1 .d − 1 after adjustment for body mass. The physiologic requirements for iron in the first, second, and third trimesters were 2.04 mg.d − 1 , 3.26 mg.d − 1 , and 4.13 mg.d − 1 , respectively. When adjusted for body mass, the physiologic requirements for iron in different trimesters were 32.3 μg.kg − 1 .d − 1 , 46.9 μg.kg − 1 .d − 1 , and 55.7 μg.kg − 1 .d − 1 , respectively. Conclusion We preliminarily explored the physiologic requirement for iron in pregnant women. The data demonstrated that pregnant women needed about twice iron than non-pregnant women. This research may be helpful for the design of future studies and the modification of iron DRIs. Trial registration ChiCTR, ChiCTR-OCH-14004302. Registered 14 February 2014, http://www.chictr.org.cn/showproj.aspx?proj=5267